2016
DOI: 10.1186/s41100-016-0034-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of hypertension for patients undergoing dialysis therapy

Abstract: Hypertension is very prevalent among patients undergoing dialysis therapy: hemodialysis (HD) and peritoneal dialysis (PD). Although it is recognized as a great risk of cardiovascular mortality for these populations, how to regulate blood pressure (BP) is poorly understood. For HD patients, we should pay much attention to methods of measuring BP. Outof-center BP levels and BP variability should be evaluated by ambulatory BP monitoring and home BP measurement because they are closely associated with cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 78 publications
0
13
0
2
Order By: Relevance
“…Several studies have shown a "U-shape" relationship between high blood pressure and mortality, implying that blood pressure levels below certain range is more harmful than higher levels (Carney, 2013). Hypertension being multifactorial in nature and this reverse epidemiology of blood pressure and mortality makes it difficult to determine blood pressure targets especially in highrisk patients such as ESRD patients on hemodialysis (Taniyama, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown a "U-shape" relationship between high blood pressure and mortality, implying that blood pressure levels below certain range is more harmful than higher levels (Carney, 2013). Hypertension being multifactorial in nature and this reverse epidemiology of blood pressure and mortality makes it difficult to determine blood pressure targets especially in highrisk patients such as ESRD patients on hemodialysis (Taniyama, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…ст. -62 и 28 % соответственно [26,27]. Столь высокая частота неконтролируемой АГ у пациентов с ТПН объясняется гемодинамической перегрузкой, повышенной активностью РААС и симпатической нервной системы, гиперпаратиреозом и кальцификацией артерий [24].…”
Section: Discussionunclassified
“…This means the removal of fluid during HD creates a less drastic fluid shift between the intracellular, interstitial, and extracellular space. Excessive salt and water play a critical role in raising the BP of HD patients [ 18 , 19 ]. Since cardiovascular complications are the major causes of mortality and morbidity in HD patients, salt and water can be considered as the most important “uremic toxins,” because their retention is of huge concern and has a great impact on the lives of patients.…”
Section: Discussionmentioning
confidence: 99%